Schools Past and Present - Dinmont, Kerry, 1982- (Minneapolis : Lerner Publications, 2019)
How is everyday life today different from in the past? Learn about what has changed and what has stayed the same.
School through history -- The and now -- Picture glossary -- Read more Index.
Includes index
Keywords: Schools -- Juvenile literature; Schools -- Juvenile literature -- History; Schools; Instructional and educational works; History